A study to correlate admission non stress test and immediate post-partum umbilical cord arterial pH with neonatal outcome - Nainani, Rakhi; Athwani, Vivek; Avasthi, Kumkum; Bansal, Venus; Sharma, Pardeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Continuous electronic fetal monitoring in labour has become a standard practice in developed countries; this may not be possible in low middle-income countries. So, this study was conducted to correlate admission non stress test (NST) and immediate post-partum umbilical cord arterial (UCA) pH with neonatal outcome. Methods: This prospective observational study was conducted at tertiary care centre in North India. After informed and written consent, 100 pregnant women with singleton live pregnancy of gestational age ≥32 weeks admitted in labour, were subjected to admission NST and immediately after delivery sample for UCA pH was taken. Clinically relevant neonatal outcome was correlated with admission NST and UCA pH. Appropriate statistical tests were used and p-value <0.05 taken as significant. Results: Admission NST was normal, suspicious, pathological in 67%, 27%, 6% subjects, respectively. Study found statistically significant correlation between admission NST and UCA pH with neonatal outcomes (i.e. fetal distress, need of advanced resuscitation, delayed oral feeding). Fetal distress was seen in 9 newborns, in these 8 delivered by CS and 1 required ventous application. Admission NST had high sensitivity (88.89%) and NPV (98.5%) for detection of fetal distress. The optimal cut off for pH and lactate was 7.25 and 2.55 mmol/L, respectively to predict fetal distress. Conclusions: Admission NST can be considered as a screening modality to detect fetus in distress and it showed good correlation with umbilical cord arterial pH for predicting short term neonatal outcome.